Systemic organization development - Grossmann, Ralph; Scala, Klaus; Bauer, Gunther (Emerald Publishing Limited : IAP - Information Age Publishing, inc., 2018)
This book presents - for the first time in the English language - the concept of systemic organization development and its use in management and consultancy. It demonstrates in a succinct and compact way, how the systemic approach, in its up-to-date version, is well suited to describe and handle complex challenges in diverse organizations of all sectors of society.First, the authors sketch out the crucial role organizations play today and the increasing importance of their ability to change.The central theme of the book is thus the design of organizational change processes with the help of different tools. These tools deal cautiously with employees, clients and cooperation partners in order to ensure sustainable success of an organization.In the final chapters the authors delve into specific attitudes during the change process, such as the building of trust and the allowing of emotions. Several cases illustrate how the concept and the tools promote organizational development. The book well provides a practical guideline.Additionally, the book talks about important aspects managers have to pay attention to, such as dealing with concerns and resistance. The values of the systemic concept like sustainability, selective participation and growth from inside are convincingly exemplified.The book is theoretically sound and grounded by the authors' long management and consulting experience and their research activities with the university background. It is addressed mainly at actors in corporations, not-for-profit and public organizations, who's task it is to organize, design and effectuate change while the daily business continues alongside. These actors may be leaders, managers, experts, consultants, project managers or employees.